Effect of nitrogen fertilization on morphological and biochemical traits of some Apiaceae crops under arid region conditions in Egypt - KHALID ALI KHALID (Smujo International, 2013)
Khalid KA. 2013. Effect of nitrogen fertilization on morphological and biochemical traits of some Apiaceae crops under arid region conditions in Egypt. Nusantara Bioscience 5: 15-21. Arid regions in Egypt are characterized by poor nutrients content and unfavorable environmental conditions which negatively affect growth and productivity of medicinal and aromatic plants including anise, coriander and sweet fennel. So the main objective of the present investigation was to study the effect of different levels of N, namely 0 (control), 100, 150 and 200 kg ha-1 used as ammonium sulphate [(NH4)2SO] (20% N), on selected morphological and biochemical characteristics of anise, coriander and sweet fennel plants cultivated under arid regions conditions during two successive seasons. The most effective dose of nitrogen was 200 kg ha-14 of N, resulting in a positive increase in vegetative growth characters and content of essential oil, fixed oil, total carbohydrates, soluble sugars, protein and nutrients (NPK).